Analysis of the cyclic tensile behaviour of an elasto-viscoplastic polyvinylidene fluoride (PVDF). (May 2018) - Motta, E.P.; Reis, J.M.L.; da Costa Mattos, H.S.
Abstract: The present paper aims to perform an experimental and theoretical study regarding the inelastic deformation progressive accumulation observed in a polyvinylidene fluoride (PVDF) specimen machined from flexible pipe internal pressure sheaths under cyclic load-unload tensile tests and in monotonic tensile tests. Experiments show that the elastic mechanical behaviour is not rate-dependent because the Young's modulus does not suffer a considerable variation with change in the strain rate. However, the strain hardening induced by the plastic deformation is strongly rate-dependent. Hence, the mechanical behaviour of this polymer is not elasto-plastic or viscoelastic, but elasto-viscoplastic. Also, the kinematic hardening strongly increases with growth of accumulated inelastic strain, making it much more significant than the isotropic hardening. This paper proposes an elasto-viscoplastic mechanical model capable of describing the cyclic and monotonic inelastic behaviour for an arbitrary loading history. The kinenatic hardening observed for this PVDF makes it possible to identify experimentally all material parameters that arise in the model by performing load-unload tests using flat specimens, eliminating buckling problems and the need to control eventual misalignment in the universal test machine grips. Good agreement was noted when comparing the theoretical results with experiments. Highlights: The cyclic inelastic behaviour of an PVDF is analysed. The mechanical behaviour of this polymer is not viscoelastic, but elasto-viscoplastic. Experiments show that the elastic properties are not rate-dependent. The kinematic hardening it more significant than the isotropic hardening. The preliminary model is in good agreement with experiments.